Rationale, Design, and Structure of UMSEP Courses - Ai Chin Cecilia Goon (Journal of Modern Languages)
This paper considers the UMSEP courses and materials design in five sections, as: principles underlying course design; key design features; syllabus structure; and, unit structure variations among the courses. The paper points to the framework for course design, which has evolved from the pragmatic application of research findings to solve specific needs.